Conundrums of supported living: The experiences of people with intellectual disability. Issue 4 (2nd October 2017) - Bigby, Christine; Bould, Emma; Beadle-Brown, Julie
ABSTRACT: Background Dissatisfaction with the inflexibility of the group home model has led to the growth of supported living that separates housing from support and is thought to have greater potential for better quality of life outcomes. Comparative studies have had mixed findings with some showing few differences, other than greater choice in supported living. By investigating service user experiences of supported living this study aimed to identify how the potential of supported living might be better realised. Method Thirty-four people with intellectual disability participated in 7 focus group interviews and 6 people in an individual interview. Data were analysed using grounded theory methods. Results Although participants experienced greater choice and control over their everyday lives, they did not feel they controlled the way support was provided and experienced restrictions on lifestyle associated with low income. Despite their use of community places and varied social connections to family, friends, and acquaintances, most experienced loneliness. Conclusions If the potential of supported living is to be realised, shortcomings of support arrangements must be addressed by, for example, greater consistency of support worker skills, consumer control over recruitment and rostering, and more skilled support to build friendships and manage difficult relationships.